2019
DOI: 10.1017/s104161021900053x
|View full text |Cite
|
Sign up to set email alerts
|

Validation of the Cohen-Mansfield Agitation Inventory Observational (CMAI-O) tool - ERRATUM

Abstract: The above article (Griffiths et al., 2019) published with an incorrect abstract.The correct abstract is as follows:Objectives:Behaviours associated with agitation are common in people living with dementia. The Cohen-Mansfield Agitation Inventory (CMAI) is a 29-item scale widely used to assess agitation completed by a proxy (family carer or staff member). However, proxy informants introduce possible reporting bias when blinding to the treatment arm is not possible, and potential accuracy issues due to irregular… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 1 publication
0
3
0
Order By: Relevance
“…Agitation is defined as "inappropriate verbal, vocal or motor activity, which is not an expression of unmet need, and encompasses physical and verbal aggression" [4]. Agitation is not a diagnostic term, but a term used by clinicians to indicate an individual's response to a symptom or behaviors that reflect a person's reaction to the care or their environment [5]. Agitation, which produces feelings of anger and helplessness, can negatively affect not only such patients, but also the quality of life (QOL) of their families and caregivers [6].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Agitation is defined as "inappropriate verbal, vocal or motor activity, which is not an expression of unmet need, and encompasses physical and verbal aggression" [4]. Agitation is not a diagnostic term, but a term used by clinicians to indicate an individual's response to a symptom or behaviors that reflect a person's reaction to the care or their environment [5]. Agitation, which produces feelings of anger and helplessness, can negatively affect not only such patients, but also the quality of life (QOL) of their families and caregivers [6].…”
Section: Introductionmentioning
confidence: 99%
“…The incidence of agitation behavior varies slightly from study to study, but agitation behav-iors are observed in 83 to 96% of all long term care facility residents and in 56 to 98% of home-based patients with dementia living in communities [7]. Patients who display the symptoms of agitation with dementia can cause their caregivers and others around them severe distress [5]. Since agitation in dementia has many different etiologies and because people with agitation in dementia are often unable to accurately recall or report their experiences, a full and careful assessment is essential [5].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation